2017
DOI: 10.1111/ecot.12138
|View full text |Cite
|
Sign up to set email alerts
|

How house price appreciation affects homeowners' labour force participation

Abstract: This paper investigates the effects of house price appreciation on homeowners' labour force participation (LFP). Although economic theories predict that housing capital gains will reduce labour supply, empirical evidence from urban China revealed that house price appreciation significantly boosts homeowners' LFP. Heterogeneous analyses indicate that LFP behaviour is more likely to be affected by house price appreciation for female and younger homeowners. Furthermore, homeowners living in provinces with greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…They concluded that a rise of 10,000 RMB in housing value reduces the likelihood of female homeowners joining the labor force by 1.37 percentage points, while increasing the likelihood of becoming housewives by 1.49 percentage points. Similarly, Zhao et al (2018) discovered that rising housing prices boost the labor supply in urban China. They also concluded that rising housing prices have a greater impact on women and the younger labor supply.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that a rise of 10,000 RMB in housing value reduces the likelihood of female homeowners joining the labor force by 1.37 percentage points, while increasing the likelihood of becoming housewives by 1.49 percentage points. Similarly, Zhao et al (2018) discovered that rising housing prices boost the labor supply in urban China. They also concluded that rising housing prices have a greater impact on women and the younger labor supply.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The shifting demographics heightened competition in the marriage market. Given that housing is a significant cost associated with marriage and that marriage is one of the most important goals for young people, an increase in housing costs will encourage young people (especially females) to enter the labor force (Zhao et al, 2018 ). Furthermore, after a decade of consistent price growth, people now believe that buying a home is one of the most secure forms of investment.…”
Section: Empirical Analysismentioning
confidence: 99%